The Effect of High-Quality Nursing Management on Thyroid Tumor Patients after Bipolar Coagulation. (19th March 2022) - Ji, Yanting; Zhang, Buyong; Zhang, Xuan; Xue, Lingbo; Shi, Qingfeng; Li, Jie
Abstract : Objective . To evaluate the effect of high-quality nursing on thyroid tumor patients after bipolar coagulation and its impact on nursing satisfaction. Methods . From January 2019 to January 2020, 90 patients with thyroid tumors treated with bipolar coagulation in our hospital were identified as the study objects and randomized to the control group (n = 45 ) and the experimental group (n = 45 ) random number table method. Both groups received conventional nursing, and the experimental group additionally adopted high-quality nursing. The incidence of postoperative complications and nursing satisfaction between the two groups was compared. The Exercise of Self-Care Agency Scale (ESCA) was used to assess the self-care ability of patients after the intervention, and the Generic Quality of Life Inventory-74 (GQOLI-74) was used to evaluate the quality of life of the two groups of patients after the intervention. The Hospital Anxiety and Depression (HAD) scale was adopted to evaluate the emotional state of the patient before and after the intervention, and the Numerical Rating Scale (NRS) was employed to evaluate the pain intensity of the patient after the intervention. Counting data was analyzed by the X2 test, and the measurement data was analyzed by t-test. Results . After the intervention, the total incidence of postoperative complications in the experimental group was significantly lower than that in the control group (11.11% versus 33.33%, P < 0.05 ). The experimental group obtained remarkably higher nursing satisfaction (93.33% versus 71.11%), ESCA scores, and GQOLI-74 scores than the control group (P < 0.05 ). Lower HAD scores were observed in the experimental group than those of the control group (P < 0.001 ). Lower HAD scores were observed in the experimental group than those of the control group (P < 0.001 ). The NRS score of the experimental group was significantly lower than that of the control group 12 h and 24 h after the intervention (P < 0.001 ). Conclusion . High-quality nursing for patients with thyroid tumors can effectively alleviate the negative emotions, improve the quality of life, and contribute to a harmonious nurse-patient relationship, which is worthy of promotion and application.